Pengaruh Kepuasan Kerja dan Fasilitas Kerja terhadap Kualitas Pelayanan di Lingkungan Dinas Sosial Provinsi Kalimantan Timur - Aang Larassanti; Mursidah Nurfadillah; Fenty Fauziah (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2025)
Service quality is an important element in creating organizational excellence, which not only reflects the organization's performance but also the satisfaction of the community as a service user. Factors such as tangible, reliability, responsiveness, assurance, and empathy are the benchmarks in assessing service quality. On the other hand, employee job satisfaction is influenced by various factors such as work atmosphere, relationships between colleagues, career paths, and compensation, which directly impact their motivation and performance. In addition, adequate work facilities are an important support in supporting employee performance to be more optimal and efficient. In this study, a quantitative approach was used with a survey method, collecting data from questionnaires distributed to 50 respondents. This study aims to determine the influence of job satisfaction and work facilities on the quality of services within the East Kalimantan Provincial Social Service. The research method used is quantitative descriptive with data collection techniques through interviews and distribution of questionnaires to Social Service employees. The results of the partial test showed that job satisfaction had a positive and significant effect on service quality. Likewise, work facilities also have a positive and significant effect on the quality of service. Furthermore, simultaneous tests showed that job satisfaction and work facilities together had a significant effect on service quality. The results of this study indicate that increasing job satisfaction and work facilities can encourage the creation of more optimal service quality within the East Kalimantan Provincial Social Service.